Effect of Depotash Vinasse on Rumen Fermentation Kinetics in vitro - Singh, Gaurav Pratap; L, Vandana Kumari; Sharma, Amit N; Mohini, Madhu; Arora, Naresh; Mondal, Goutam (Indian Journal of Animal Nutrition, 2020)
Vinasse is an industrial byproduct of distilleries which may be used in animal feeding otherwise a pollutant of water and soil. An in vitro experiment was conducted to observed the effect of molasses and depotash vinasse on rumen fermentation parameters (IVDMD, IVOMD, NH3-N, PF and MBP). Concentrate mixture, pellet with molasses (Pellet M) and pellet with depotash vinasse (pellet DPV) was prepared with same ingredients while in pellet M contained 8% molasses and pellet DPV contained 8% depotash vinasse with little change of ingredients, though chemical composition was similar. The substrate for the in vitro experiment comprised of concentrate, pellet M, pellet DPV and TMRs with concentrate/ pellets, oat, wheat straw in different proportions (40:40:20). The results revealed no noticeable changes occurred due to addition of depotash vinasse and molasses pellets (upto 8%) on rumen fermentation parameters. DM, OM and CP digestibility was similar in all the groups. Microbial biomass production and ammonia nitrogen was also similar in all the groups. It was concluded that depotash vinasse can be used in pellet making and subsequent feeding to animals without any harmful effect on rumen fermentation parameters.